Thermal comfort and overcrowding in bamboo cane-enveloped housing in Portoviejo - Cobeña-Loor, David; Moreira-Macías, Lyli (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
The objective was to analyze the relationship between thermal comfort and the occupancy rate of homes with bamboo envelopes in the city of Portoviejo, as well as to understand how these factors influence residents’ thermal perception. The research was quantitative. The ASHRAE Thermal Sensation and Satisfaction Scale was applied, based on a sample of 161 urban homes. The results showed that envelope material affects thermal perception, with bamboo being one of the most thermally efficient solutions when compared to concrete. The occupancy rate had no significant statistical correlation with thermal comfort, but it may have an influence. Thus, it is concluded that a bioclimatic design and the use of materials with adequate insulating properties are key when it comes to optimizing the thermal comfort of sustainable homes.